Soil properties affected by grazing, forage rotations, and tillage in the semi-arid dryland cropping systems central Great Plains - Mauler, Payton S. (Kansas State University, 2023)
Annual forages in dryland cropping systems in the semi-arid central Great Plains could improve soil health and provide forage for livestock. A study was initiated in 2016 near Jetmore, KS to investigate tillage effects on grazed continuous winter triticale [x Triticosecale Wittm. ex A. Camus (Secale x Triticum)]. The two treatments included minimal tillage (MT) and no-till (NT). A second story was conducted from 2012 to 2022 at the Southwest Research Extension Center near Garden City, KS. The crops in the rotations included winter triticale (T), forage sorghum [Sorghum bicolor (L.) Moench] (FS) and oats (Avena sativa L.) (O). Six treatments in an incomplete factorial combination of four crop rotation and two tillage treatments include FS-FS (NT), T/FS–FS–O (NT), T/FS–FS–O (RT), T/FS–FS–FS–O (NT), T/FS–FS–FS–O (RT), T-FS-O (NT). At Jetmore, Bulk density was greater pre-till (1.31g cm⁻³) compared to the post-till (1.23 g cm⁻³) and was lower under MT (1.24 g cm⁻³) compared to NT (1.29 g cm⁻³). Minimal tillage decreased water stable aggregate mean weight diameter, increased wind erodibility, and decreased dry aggregate stable MWD. Penetration resistance was unaffected by tillage systems. No-till had greater sorptivity in 2022 compared to MT. Time to runoff was greater in 2022 compared to 2021. Infiltration rate was unaffected by tillage. Soil organic carbon (SOC) stocks on a fixed depth basis was greater in pre-till than post-till in two of three years, greater in the 5- to 15-cm depth compared to 0- to 5-cm depth, and greater in NT than MT in 2022. Soil equivalent mass SOC stocks were greater in the pre-till compared to post-till and greater in the 5- to 15-cm soil depth than the 0- to 5-cm soil depth. Soil organic carbon concentration was greater in NT than MT in 2022 and greater in the 0- to 5-cm than the 5- to 15-cm depth. Nitrate-N concentration was greater in the MT and was in greater concentration in the 0- to 5-cm depth compared to the 5- to 15-cm depth. Soil phosphorus concentrations in the soil surface were greater pre-till than post-till (884 ppm vs. 554 ppm). Soil pH was slightly lower in NT compared to MT. Early forage biomass was greater in MT compared to NT, but consistent grazing leveled out forage production. Crude protein (CP), neutral detergent fiber digestibility (NDFD), and total digestible nutrients (TDN) were greater in the spring compared to summer. However, acid detergent fiber (ADF), neutral detergent fiber (NDF), and undigested neutral detergent fiber (UNDF) were greater in the summer compared to spring. Minimal tillage increased CP, NDF, and UNDF but decreased NDFD in 2022. Minimal tillage significantly reduced weed density compared to NT. Our findings suggest that MT had minimal effects on soil physical and chemical properties, significantly decreased weed population, and increased early season forage biomass. At Garden City, results showed treatments was not different for soil parameters except total nitrogen (TN), soil nitrate (NO₃⁻) concentrations and soil potassium (K). Soil nitrate-N concentration was greatest in T/S-S-S-O (NT) and the lower nitrate concentrations in T/FS-FS-O (NT), T/FS-FS-O (RT), and T/FS-FS-FS-O (RT). Potassium concentration differed among forage rotations; T/S-S-S-O in NT had the highest level and FS-FS had the lowest level. Tillage had no significant differences in soil parameters except NO₃⁻, K and WSA MWD. No tillage had more soil nitrates and K concentration than RT. However, RT had a higher WSA MWD compared to NT. Sorptivity, infiltration rate, and TTR was not significantly different among treatment. Sorptivity was greater in NT in 2021 but was greater in RT in 2022. Similarly, infiltration rate in 2021 infiltration rate was greater in NT but was greater in RT in 2022. Time to runoff was faster in NT in 2021 but was faster in RT in 2022. Time to run-off saw that 2021 was faster in run-off time compared to 2022. Our findings suggest that forage rotations can be used without negative impacts on soil physical and chemical properties and tillage had limited impacts on soil parameters.
Keywords: Soil health; Annual forages; Forages; Soil